Cambiamento climatico e rischio Proposta per una didattica geografica - BONATI, SARA; TONONI, MARCO (Tratti geografici. Materiali di ricerca e risorse educative - Open Access, 2020)
This edited book aims to address the issues of risk and climate change in geographical education at different school levels, offering both theoretical thoughts and the proposal of teaching activities. The discussed issues are often on the margins of teaching and geography studies in Italy, although they play a pivotal role in the understanding of territories and in the shaping of economic, social and environmental policies. The aim of the volume is to recognize the geography of risk as a relevant field of research and teaching, that needs to be implemented in Italy. The chapters see the contribution of different stakeholders, like Civil Protection, NGOs (Save the Children and Red Cross Red Crescent Climate Centre), municipalities and universities, trying to challenge and reason on the role of geography in the dissemination and teaching of the topics. The experiences and activities proposed provide a first tool for school and educators, which can have practical implications as well as stimulate further works on the topic. In particular, different risks (climate change, earthquakes, multi-hazard, etc.) and methodologies are discussed, offering some examples that can be replicated and further developed by teachers at different levels.